Attitudes towards ICT in learning: a study on rural area primary school students / Siti Aminah Kusaini - Kusaini, Siti Aminah (2012)
The use of ICT in learning has been implemented by all schools in Malaysia regardless secondary or primary level. One of the main issues is the lack use of ICT in learning for any subjects in schools after the abolishment of ETeMS (English in the Teaching of Mathematics and Science) by 2012. The purpose of this study is to reveal primary students attitudes towards ICT in learning, to examine teachers influence on students interest in using ICT, to explore the relationship between male and female students' attitudes towards ICT and to examine whether there are any difference in attitudes towards ICT in learning among students from three different schools. In this correlational descriptive study, 60 students from three primary schools in Kuala Selangor, Selangor responded to the given questionnaires. A quantitative approach was used to analyze the data. The results showed that the students are still interested towards ICT in learning. Besides, teacher's influence in using ICT in learning is contributing towards their attitudes. Correlational analysis showed positive correlation between students' attitudes and teacher's influence. There is a significant difference (p < .05) in the means in the level of male and female attitudes towards ICT in learning. The result also showed that there is no significant diflFerence (p > .05) in students' interest in using ICT in learning among the three schools. Several implications of the study are teachers need to implement any ICT programmes set by the government, to make use of ICT facilities in schools into maximum as well as to keep on using the ICT in their teaching for there are many advantages that they could get from practicing technology in teaching.